Effects of Different Degrees of Extraluminal Compression on Hemodynamics in a Prominent Transverse-Sigmoid Sinus Junction - Qiu, Xiaoyu; Zhao, Pengfei; Mu, Zhenxia; Dai, Chihang; Li, Xiaoshuai; Xu, Ning; Ding, Heyu; Gong, Shusheng; Yang, Zhenghan; Gao, Bin; Wang, Zhenchang (Frontiers in Human Neuroscience, 2022)
Objectives: To simulate hemodynamic changes after extraluminal compression in pulsatile tinnitus (PT) patients with a prominent transverse-sigmoid sinus junction (PTSJ). Methods: One patient-specific case was reconstructed based on computed tomography venography images of a PT patient. The compression degree served as a new index in this study. Cases with 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80% and 90% of the compression degree of the control subject were constructed. Steady-state computational fluid dynamics were assessed. The wall pressure distribution, wall maximum pressure (Pmax) and flow pattern (velocity streamlines and velocity vector) of the PTSJ were calculated to evaluate hemodynamic differences among all cases. Results: With increasing compression, the wall pressure at the compression point and downstream of the PTSJ decreased but increased upstream. When the compression degree exceeded 70%, the upstream pressure increased significantly. At 50% compression, the blood flow pattern downstream of the sigmoid sinus tended to spiral, especially after 80% compression. Beyond 60% compression, the blood flow pattern under the compression axis became more medial. Conclusion: Mechanical compression of PTSJ changes wall pressure and blood flow patterns. The degree of compression should be carefully observed to avoid possible complications or reoccurrence.